PERAN TEKNOLOGI DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Yulianti, Yulianti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The aim of this research is to provide information to teachers about the important role of technology in mathematics education in elementary schools. Increasing teacher awareness of the importance of technology involvement in mathematics teaching in elementary schools is a solution suggested in this research. The method used in this research is the library research method. This strategy, known as library research methods, involves a series of actions related to collecting library data from books and the internet to answer the problem formulation that must be solved. Research findings show that using technology to learn mathematics has benefits. Students can use technology as a learning resource. By using technology, children can more easily understand abstract mathematical concepts by seeing them as concrete objects. Many timeless learning platforms and software are available to facilitate learning and replace the role of the instructor in the classroom. However, technology also has its drawbacks. For example, children can easily gain knowledge through the internet with hands-on solutions, and using technology can even make students less proficient in mathematics. Technology can improve learning activities if used appropriately.